Monitoring Jumlah Orang di Ruangan Menggunakan Teknologi IOT - Nurlaili, Dewi; Maulindar, Joni; Hartanti, Dwi (JATISI, 2025)
The problem addressed in this research is the need to monitor the number of people entering and exiting a meeting room automatically and accurately. The objective of this study is to develop a system for monitoring the number of people in a meeting room using IoT technology to improve the efficiency of room capacity management. The method used in this research involves the application of an Arduino Uno microcontroller with HC-SR04 ultrasonic sensors to detect object movement and display the results on an LCD in real-time. The test results show that the system successfully detects the number of objects entering and exiting the room accurately. The LCD display shows numbers corresponding to the changes in the number of people inside the room with labels "In" and "Out." The first test showed that when 25 objects entered and 6 objects exited, the remaining number of visitors was 19. In the second test, with 7 objects entering and no objects exiting, the number of visitors inside the room was 7. The third test showed 23 objects entering and 3 objects exiting, leaving 20 people in the room. The fourth test, with 14 objects entering and no objects exiting, showed 14 people inside the room. The fifth test, with 10 objects entering and no objects exiting, resulted in 10 people remaining in the room. Overall, the test results indicate that the system functions well in detecting the number of people in the room in real-time and can be used for efficient room capacity monitoring.